Cybersecurity: defending networks from evolving threats - Mykola Protsenko (Закарпатський угорський інститут імені Ференца Ракоці II., 2024)
Abstract. Cybersecurity has become critical in the modern age of rapidly digitizing information and global interconnected networks. Cyberattacks threaten the confidentiality, integrity, and availability of networks, systems, and sensitive data. These threats range from malware to ransomware, each posing a serious risk to information security.
Keywords: cybersecurity; networks